2015
DOI: 10.1080/10942912.2015.1063069
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Aspects of Determining Apple Mechanical Properties During Impact

Abstract: The influence of cylindrical sizes of samples and velocity of impact on its course and strength parameters for the "Braeburn" variety apples was studied. Three sample lengths of 17, 19, and 21 mm, three diameters of 10, 15, and 20 mm and four impact velocities of 0.25, 0.5, 0.75, and 1 ms-1 were applied. Failure stress and strain, impact energy, absorbed energy as well as tissue stiffness and toughness were determined as dependent variables. The influence of the sample diameter on maximum force response, impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The pendulum was connected with the angular displacement sensor RON 275 (Heidenhain, Traunreut, Germany) with the accuracy of 0.005°. The sensor recording inclination angle change was connected to the measuring card (SBC-68, National Instruments, Warsaw, Poland), transmitting signals to the application working in the LabView environment [ 9 , 10 , 11 , 30 ]. The right humerus was fixed with quick-drying epoxy glue in a PVC tube with an internal diameter of 15 mm and a 20 mm height.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pendulum was connected with the angular displacement sensor RON 275 (Heidenhain, Traunreut, Germany) with the accuracy of 0.005°. The sensor recording inclination angle change was connected to the measuring card (SBC-68, National Instruments, Warsaw, Poland), transmitting signals to the application working in the LabView environment [ 9 , 10 , 11 , 30 ]. The right humerus was fixed with quick-drying epoxy glue in a PVC tube with an internal diameter of 15 mm and a 20 mm height.…”
Section: Methodsmentioning
confidence: 99%
“…Zhai et al [ 4 ] analyzed the loading rate effect on the fracture toughness of porcine bone specimens and found that the fracture initiation of cortical bone decreased as the loading rate increased. The impact of free-falling mass was well described for plant tissues [ 9 , 10 , 11 ] or engineering materials [ 12 , 13 ]. With regard to bone, there are still few studies describing the mechanical parameters under the impact loading condition.…”
Section: Introductionmentioning
confidence: 99%
“…A cylindrical hammer with a 3.5 kg mass and an Endevco model 2311-100 piezoelectric force sensor of 2 mV N -1 sensitivity and a measuring range of 222.5 N was installed on the end of the pendulum (Fig. 1) (Stropek and Gołacki, 2016a;Bajema et al, 1998). An identical sensor was installed in the anvil placed on the steel plate which was fixed to the concrete bearing wall of the building.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were initially compressed along the 2 mm axes and then the steady strain was maintained while recording the force response for 30 s. The assumed test time resulted from small changes of the force response after 30 s. Stress relaxation tests under the quasi-static loading conditions were applied by means of the TA.HD plus Texture Analyser at three velocities: 0.0002, 0.002, 0.02 m s -1 . The measurements under impact loading conditions were made on an impact research stand (Stropek and Gołacki, 2016a) at the velocities of: 0.25, 0.5, and 1 m s -1 . The sample deformation size amounting to 2 mm was determined from the initial destructive compression tests taken under quasi-static loading conditions.…”
Section: Methodsmentioning
confidence: 99%